Tissue-Specific Expression of Cell Wall Proteins in Developing Soybean Tissues. - Ye, ZH (1991)
Cell wall hydroxyproline-rich glycoproteins (HRGPs) and glycine-rich proteins (GRPs) were examined at the protein and at the mRNA levels in developing soybean tissues by tissue print immunoblots and RNA blots. In young soybean stems, HRGPs are expressed most heavily in cambium cells, in a few layers of cortex cells surrounding primary phloem, and in some parenchyma cells around the primary xylem, whereas GRPs are highly expressed in the primary xylem and also in the primary phloem. In older soybean stems, HRGP genes are expressed exclusively in cambium cells and GRP genes are most heavily expressed in newly differentiated secondary xylem cells. Similar expression patterns of HRGPs and of GRPs were found in soybean petioles, seedcoats, and young hypocotyls, and also in bean petioles and stems. HRGPs and GRPs become insolubilized in soybean stem cell walls. Three major HRGP mRNAs and two major GRP mRNAs accumulate in soybean stems. Soluble HRGPs are abundant in young hypocotyl apical regions and young root apical regions, whereas in hypocotyl and root mature regions, soluble HRGPs are found only in a few layers of cortex cells surrounding the vascular bundles. GRPs are specifically localized in primary xylem cell walls of young root. These results show that the gene expression of HRGPs and GRPs is developmentally regulated in a tissue-specific manner. In soybean tissues, HRGPs are most heavily expressed in meristematic cells and in some of those cells that may be under stress, whereas GRPs are expressed in all cells that are or are going to be lignified.